Multivalued Usco Functions and Stegall Spaces - Narváez, Diana Ximena (Revista de Ciencias, 2018)
In this article we consider the study of the -differentiability and -ifferentiability for convex functions, not only in the general context of topological vector spaces (), but also in the context of Banach spaces. We study a special class of Banach spaces named Stegall spaces, denoted by , which is located between the Asplund -spaces and Asplund -spaces (-Asplund). We present a self-contained proof of the Stegall theorem, without appealing to the huge number of references required in some proofs available in the classical literature (4). This requires a thorough study of a very special type of multivalued functions between Banach spaces known as usco multi-functions.